Digital technologies, sustainable lifestyle, and tourism: How digital nomads navigate global mobility? - Francisco Javier S. Lacárcel (Sustainable Technology and Entrepreneurship)
This article explores how digital platforms facilitate entrepreneurship and enable global mobility for digital nomads, i.e., individuals who work remotely while residing in various locations worldwide. The specific focus is on how these platforms influence digital nomads’ decision making related to destination choices and entrepreneurial ventures, while also highlighting opportunities for the adoption of sustainable technology to enhance flexibility and efficiency of remote work. To this end, a total of 25 in-depth interviews were conducted with digital nomads, platform representatives, and academics. Interview questions focused on the impact of digital tools on professional practices and the nomadic lifestyle. The data were analyzed using Latent Dirichlet Allocation (LDA) topic modeling, combined with Computer-Aided Text Analysis (CATA), and Natural Language Processing (NLP) techniques. Based on the results, 20 key topics related to the challenges, motivations, and future trends of this community were identified, including, among others, digital comfort, sustainable mobility, technology, digital environment, work-life balance, and workspace issues or employment. Taken together, the findings provide valuable insights into the intersection of digital nomadism and digital platforms and technologies, contributing to theories such as work-life balance, sustainable technology use, and boundary work.